FORMATION DYNAMICS OF THE MIDDLE RIPHEAN RIFTOGENIC STRUTURE (WESTERN SLOPE OF THE SOUTHERN URALS) - Kovalev S.G. (My University, 2004)
Based on the model of continental riftogenesis the Middle Riphean evolution of the study region was marked by the confinement of the maximal tension to its central part and the formation of grabens filled with coarse- to fine-grained terrigenous material. The brittle cleaving of the upper crustal layers as a result of the rifting promoted the formation of tectonic relief zones, which served as conduits for magmatic melts, and the advanced alteration of substrate by fluids. Such environments stimulate intense and diverse (intrusive, effusive, and pyroclastic) manifestations of volcanism. Differentiation of the subcrustal chamber and probable contamination of its upper part produced magmas with different contents of the basic component (basalts and rhyolites) aand geochemical characteristics. In our case, the rifting is advanced, but the continental crust entirety has not been destroyed (the model of continental rift as an area of extreme tension.
Keywords: Riphean; Precambrian::Proterozoic::Riphean; Докембрий::Протерозой::Рифей